Control of Gastrointestinal Nematodes Infection in Small Ruminants by Nematophagous Fungi - Ahmad, Riza Zainuddin; ., Beriajaya; Hastiono, S (Indonesian Animal Sciences Society, 2002)
The disease caused by gastrointestinal nematodes infection in small ruminants in Indonesia is quite unprofitable. Control with anthelmintic developed a negative effect of anthelmintic resistance and residue in tissue if anthelmintic are given routinely. Biological control is one of the control methods using microorganisms especially molds. The moulds can form traps and destroy the body of larvae and eggs by hife and produce toxins. Few isolates of nematophagous fungi such as Arthrobotrys spp. and Monacrosporium spp. were found from surveys done in West Java. Applications of these fungi as biological control against nematodiasis is promising as indicated from in vitro and in vivo studies. Â Key words: Biological control, nematophagous fungi, small ruminants